2004
DOI: 10.1590/s0103-97332004000300027
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology: an information-theoretic-based thermo-statistical approach

Abstract: Systems Biology (system-level understanding in biological science), from the physical-chemical point of view, is involved with irreversible thermodynamics and nonlinear kinetic theory of open systems which are founded on nonequilibrium statistical mechanics. We describe a modern thermo-statistical approach for dealing with complex systems, in particular biological systems. We consider the case of a very peculiar complex behavior in open boson systems sufficiently away, from equilibrium, which appear to have la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
0
16
0
1
Order By: Relevance
“…Reimers (2009) have properties of specific energy sources as reported by Mesquita et al (2004) by which, weak coherent condensates within individual proteins may be feasible. They also showed how weak condensation can lead to a significant deviation from the simple steady-state, expected when biochemical processes provide energy to an enzyme.…”
Section: The Role Of Informational Ca2+ Ion Messenger In the Creationmentioning
confidence: 99%
“…Reimers (2009) have properties of specific energy sources as reported by Mesquita et al (2004) by which, weak coherent condensates within individual proteins may be feasible. They also showed how weak condensation can lead to a significant deviation from the simple steady-state, expected when biochemical processes provide energy to an enzyme.…”
Section: The Role Of Informational Ca2+ Ion Messenger In the Creationmentioning
confidence: 99%
“…The reason that water plays an important role in life is because in living systems it is known to support coherent dipolar excitations where the Fröhlich effect has a connection with long range propagation of signals in biological and nonbiological materials as wave packets consisting Schrodinger Davydov solitons (Mesquita et al, 2004;2005;Fröhlich Centenary International Symposium, 2005). Excitations are of great importance in the migration of energy and for the quantum computation of early life.…”
Section: Quantum Biologics Led To the Origin Of Life And Consciousnesmentioning
confidence: 99%
“…In Refs. [158][159][160][161][162][163][164][168][169][170][171][172][173] is given an overview of the role of the irreversible thermodynamics based on NESEF in dealing with biosystems. On the question of the relation of Biology and Physics we may say that the sometimes mentioned gap between both disciplines has been slowly shrinking along recent decades.…”
Section: Coherent States and Nonequilibrium Bose-einstein-like Conmentioning
confidence: 99%
“…The question was further pursued in [158,[168][169][170][171][172], where the above mentioned Fröhlich effect -consisting, as noticed, of a coherent behavior of boson-like excitations in biological and molecular polymers -is fully derived and analyzed in terms of NESEF. It was shown that when double (or multiple) processes of excitation of the boson system are possible there follows a positive-feedback phenomenon that greatly favors and enhances the effect [174].…”
Section: Coherent States and Nonequilibrium Bose-einstein-like Conmentioning
confidence: 99%
See 1 more Smart Citation